Significant relationships between a simple marker of redox balance and lifestyle behaviours; Relevance to the Framingham risk score - Seyedsadjadi, Neda (PLoS One, 2017)
Oxidative stress has been closely linked to the progressive cell damage associated with emerging non-communicable disease (NCDs). Early detection of these biochemical abnormalities before irreversible cell damage occurs may therefore be useful in identifying disease risk at an individual level. In order to test this hypothesis, this study assessed the relationship between a simple measure of redox status and lifestyle risk factors for NCDs, and the population-based risk score of Framingham. In a cross-sectional study design, 100 apparently healthy middle-aged males (n = 48) and females (n = 52) were asked to complete a comprehensive lifestyle assessment questionnaire, followed by body fat percentage and blood pressure measurements, and blood collection. The ratio of plasma total antioxidant capacity to hydroperoxide (TAC/HPX) was used as an index of redox balance. One-way ANOVA and multiple linear regression analysis were performed to analyse the association between TAC/HPX, lifestyle components and other plasma biomarkers. The TAC/HPX ratio was higher in males compared to females (t(96) = 2.34, P = 0.021). TAC/HPX was also lower in participants with poor sleep quality (t(93) = 2.39, P = 0.019), with high sleep apnoea risk (t(62.2) = 3.32, P = 0.002), with high caffeine (F(2, 93) = 3.97, P = 0.022) and red meat intake (F(2, 93) = 5.55, P = 0.005). These associations were independent of gender. Furthermore, the TAC/HPX ratio decreased with increasing body fat percentage (F(2, 95) = 4.74, P = 0.011) and depression score (t(94) = 2.38, P = 0.019), though these associations were dependent on gender. Importantly, a negative association was observed between TAC/HPX levels and the Framingham risk score in both males (r(45) = -0.39, P = 0.008) and females (r(50) = -0.33, P = 0.019) that was independent of other Framingham risk score components. Findings from this study suggests that a relatively simple measure of redox balance such as the TAC/HPX ratio may be a sensitive indicator of redox stress, and may therefore serve as a useful biomarker for assessing an individual’s specific NCD risk linked to unhealthy lifestyle practices.